The structure and content of Das Kapital - Deepankar Basu (University of Massachusetts, Department of Economics, 2017)
Karl Marx's magnum opus, Das Kapital, presents an analysis of the long run dynamics of a mature capitalist economy. The analysis is conducted at two primary levels of abstraction - "capital in general" (where competition between individual capitals is abstracted from) and "many capitals" (where the phenomenon of competiton between individual capitals is introduced) - and the presentation is organized into three volumes. In terms of structure, the analysis in the first two volumes is located at the level of "capital in general" and the analysis in the third volume is located at the level of "many capitals". In terms of content, the first volume analyses the production and accumulation of surplus value, the second volume investigates the problems of realization of surplus value, and the third volume analyses the mechanisms that lead to the distribution of surplus value into income streams of different fractions of the ruling class - as profit of enterprise, commercial profit, interest and rent (and monopoly profit more generally). The three volumes together give a comprehensive picture of the workings of a mature capitalist economy and highlights its long run, contradictory tendencies.
Keywords: B14; B24; B51; 330; value; surplus value; capital; reproduction schemes; prices of production; rent; interest; commercial profit